2017
DOI: 10.1080/2162402x.2017.1397250
|View full text |Cite
|
Sign up to set email alerts
|

Cancer vaccine based on a combination of an infection-enhanced adenoviral vector and pro-inflammatory allogeneic DCs leads to sustained antigen-specific immune responses in three melanoma models

Abstract: Autologous patient-derived dendritic cells (DCs) modified ex vivo to present tumor-associated antigens (TAAs) are frequently used as cancer vaccines. However, apart from the stringent logistics in producing DCs on a patient basis, accumulating evidence indicate that ex vivo engineered DCs are poor in migration and in fact do not directly present TAA epitopes to naïve T cells in vivo. Instead, it is proposed that bystander host DCs take up material from vaccine-DCs, migrate and subsequently initiate antitumor T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Although melanoma antigens recognized by Bregs were not identified, investigations into the drivers of immune responses to melanoma elucidated several antigenic epitopes derived from human melanocyte lineage-specific proteins (MART-1/Melan-A, gp100, gp75, and tyrosinase) recognized by T cells (Bakker et al, 1994;Cole et al, 1994;Kawakami et al, 1994;Topalian et al, 1996). Fotaki et al (2018) found that infection-enhanced adenovirus encoding gp100 and allogenic dendritic cells stimulated the proliferation of endogenous gp100-TCR þ T cells, resulting in delayed melanoma growth and prolonged survival (Fotaki et al, 2018). Therefore, the identification of antigens recognized by Bregs may provide insight into the mechanisms by which Breg responses are triggered and inhibit anti-melanoma immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Although melanoma antigens recognized by Bregs were not identified, investigations into the drivers of immune responses to melanoma elucidated several antigenic epitopes derived from human melanocyte lineage-specific proteins (MART-1/Melan-A, gp100, gp75, and tyrosinase) recognized by T cells (Bakker et al, 1994;Cole et al, 1994;Kawakami et al, 1994;Topalian et al, 1996). Fotaki et al (2018) found that infection-enhanced adenovirus encoding gp100 and allogenic dendritic cells stimulated the proliferation of endogenous gp100-TCR þ T cells, resulting in delayed melanoma growth and prolonged survival (Fotaki et al, 2018). Therefore, the identification of antigens recognized by Bregs may provide insight into the mechanisms by which Breg responses are triggered and inhibit anti-melanoma immunity.…”
Section: Discussionmentioning
confidence: 99%
“…CALR) or type I IFN. 57,119,214,221,224,231,255 Alongside general immunological defects, there can also exist disruption in the detection of DAMPs that are normally emitted by cancer cells undergoing ICD. 256 Such conditions include: (1) a prominent immunological tolerance determined by the specific anatomical location of the tumor (as in the case of the brain, mucosal surfaces and other immunologically privileged sites); 129,[257][258][259] (2) an abundant and persistent release of immunosuppressive cytokines such as IL10; [260][261][262][263][264] (3) a robust production of factors that favor immune exclusion, such as transforming growth factor beta 1 (TGFB1); [265][266][267][268][269][270] (4) abundant tumor infiltration by immunosuppressive immune cells like myeloid-derived suppressor cells (MDSCs); [271][272][273][274][275][276][277][278][279][280][281] (5) elevated expression of coinhibitory receptors, such as programmed cell death 1 (PDCD1, best known as PD-1) and hepatitis A virus cellular receptor 2 (HAVCR2, best known as TIM-3); [271][272][273][282][283][284] (6) lymphoid T cell depletion as a consequence of vascular exclusion;…”
Section: Introductionmentioning
confidence: 99%
“…Experimental animal models also proved to be reliable sources of data concerning (i) the screening for novel antimelanoma agents: temozolomide (B16F10 metastatic melanoma model) [ 66 , 67 ], thymoquinone (B16F10 intracerebral melanoma model using C57BL/6J mice as host) [ 68 ], oncolytic herpes simplex virus HF10, and dacarbazine combined therapy (DBA/2 mice subcutaneously inoculated with clone M3 mouse melanoma cells) [ 69 ], gliotoxin (a xenograft mouse model using athymic mice) [ 70 ], recombinant methioninase [ 71 ], cancer vaccines [ 72 ], natural compounds [ 73 , 74 ]; (ii) molecular discovery—the comprehension of melanoma metastatic pathway involving microvascular environment [ 75 ]; and (iii) in vivo tracing of melanocytic lineage cells [ 76 ].…”
Section: Murine Models Of Melanomamentioning
confidence: 99%